Role of melatonin in reducing water avoidance stress-induced degeneration of the gastrointestinal mucosa - (:unkn) unknown (WILEY, 2004)
We investigated the role of melatonin on water avoidance stress (WAS)-induced degeneration of the gastric, ileal and colonic mucosa. Wistar albino rats were exposed to acute WAS (aWAS group) or chronic WAS (cWAS group). Before exposing animals to acute (aWAS + mel group) or chronic WAS (cWAS + mel group), 10 mg/kg melatonin was injected i.p. The stomach, ileum and colon samples were investigated under light and scanning electron microscope. Malondialdehyde (MDA) and glutathione (GSH) levels were also determined. In both aWAS and cWAS groups, the epithelium of stomach showed ulceration in some areas, dilatations of the gastric glands and degeneration of gastric glandular cells; prominent congestion of the capillaries after WAS was apperent. In the cWAS group, severe vascular congestion was observed along with degeneration of ileal and colonic epithelium. MDA levels were increased and GSH levels were decreased in all tissues in both the aWAS and cWAS groups. The morphology of gastric, ileal and colonic mucosa in both aWAS + mel and cWAS + mel groups showed that the indole significantly reduced degeneration of the gastrointestinal mucosa. Decreased MDA and increased GSH levels were observed in the WAS + mel groups. Based on the results, melatonin treatment significantly prevented WAS induced degenerative morphological and biochemical changes of gastrointestinal mucosa.
Keywords: gastrointestinal tract; glutathione; lipid peroxidation; melatonin; morphology; water avoidance stress; COLD-RESTRAINT; BLOOD-FLOW; LIPID-PEROXIDATION; EPITHELIAL BARRIER; GASTRIC-MOTILITY; GLUTATHIONE; RATS; INFLAMMATION; SECRETION; PROTECTS